THE EFFECT OF PHET SIMULATION MEDIA ON CRITICAL THINKING SKILLS IN ELECTRICAL CIRCUIT MATERIAL - Daradinanti Ansori; Prima Mutia Sari (PIONIR: JURNAL PENDIDIKAN, 2025)
Finding out how PhET simulations affect the critical thinking abilities of fifth-grade electrical engineering students at SDN Slipi 11 Jakarta Barat is the goal of this study.  A quasi-experimental design with a pretest-posttest control group design is the research methodology employed.  All fifth-grade students make up the study population, and the sample is divided into two classes: a control class that uses traditional instruction and an experimental class that uses PhET simulations. Descriptive tests to measure critical thinking skills that had undergone validity and reliability testing served as the instruments.  The normality and homogeneity tests were completed before the hypothesis test.  The data were homogeneous and regularly distributed, according to the hypothesis test results. With a significance value of 0.001 (<0.05), the Independent Sample t-test hypothesis test rejected H₀.  This demonstrates how using PhET simulations significantly enhances students' capacity for critical thought.  PhET simulations also promote active student participation and enhance the interactiveness and enjoyment of learning.  PhET simulations could therefore develop into a cutting-edge teaching tool for science in elementary schools. Keywords: PhET Simulation, Critical Thinking, Electrical Circuit Material